Spectrophotometric Estimation of Bicalutamide in Tablets - Sancheti, P. P. (Medknow Publications, 2008)
A simple, sensitive, rapid, accurate and precise spectrophotometric method has been developed for the estimation of bicalutamide in bulk and pharmaceutical dosage forms. Bicalutamide shows maximum absorbance at 272 nm with molar absorptivity of 2.3399×10(4) l/mol/cm. Beer's law was obeyed in the concentration range of 1.5-18 μg/ml. The limit of detection and limit of quantification were found to be 0.1 and 0.4 μg/ml, respectively. Results of analysis were validated statistically and by recovery studies.